COMPARATIVE EFFICACY OF INHALED DRUGS FORMOTEROL / BECLOMETHASONE AND FORMOTEROL / BUDESONIDE AND BRONCHIAL ASTHMA - V. A. Nikitin; O. A. Lepuchova; L. V. Vasilieva; E. P. Karpuchina (Архивъ внутренней медицины, 2016)
There were examined 86 patients aged 20 to 65 years with a diagnosis of bronchial asthma (BA). The objective is to evaluate the level of disease control, to study the effectiveness, safety and usability when used Foster (beclomethasone dipropionate and formoterol fumarate fixed combination) Combination and Foradil (formoterol fumarate and budesonide in free combination). Patients were divided into 2 groups randomly. The first group received Foster (beclomethasone dipropionate and formoterol fumarate in a fixed combination), and the second group — Foradil Combi (budesonide and formoterol fumarate in a free combination). Results of the study were assessed for 11-13 days and 3 months. The treatment showed a significant reduction in the severity of clinical symptoms in groups 1 and 2. Respiratory function after 3 months in group 1 improved to 17,4 ± 3,2% (p <0.05), and the second at 6,0 ± 3,3% (p> 0.1). Full control of the disease was achieved in one group, 48.83% of patients, and the second at 44.19% of the patients.